ETHNOBOTANY: INTEGRATING PEOPLE, NATURE, AND BUSINESS WHILE MAINTAINING BOTANICAL, CULTURAL AND ECONOMIC INTEGRITY - Flaster, T. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Bioprospecting can be called the black sheep of ethnobotany, but done well it can reduce poverty, train botanical practitioners in communities and of course offer tools to medical practitioners in any ailing nation. Lately there was a re-surgence in this discipline of botany to identify new products based on traditional knowledge. Finding the right plant that can be used as a natural product is not an easy lab task, but what about the other issues? How does bioprospecting support sustainability? This short presentation discusses one system that seems to be working even though the long-term results are still not evident.